2016
DOI: 10.1227/neu.0000000000001344
|View full text |Cite
|
Sign up to set email alerts
|

Indications and Efficacy of Gamma Knife Stereotactic Radiosurgery for Recurrent Glioblastoma: 2 Decades of Institutional Experience

Abstract: Background The role of stereotactic radiosurgery (SRS) for recurrent glioblastoma and the radionecrosis risk in this setting remain unclear. Objective To perform a large retrospective study to help inform proper indications, efficacy, and anticipated complications of SRS for recurrent glioblastoma. Methods We retrospectively analyzed patients who underwent Gamma Knife SRS between 1991 and 2013. We used the partitioning deletion/substitution/addition (partDSA) algorithm to identify potential predictor covar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 83 publications
3
17
0
5
Order By: Relevance
“…With respect to the retrospective nature and small numbers of patients, available data suggest increased survival rates with SRS and systemic therapies compared to SRS alone [ 38 , 44 , 46 , 48 , 51 ]. The reported overall survival time after concurrent SRS and temozolomide is around 9–15 months; some [ 44 , 46 , 48 , 51 ], but not all [ 36 , 47 ], studies showed significant survival benefit following chemoradiation over SRS alone, especially in patients with O 6 -methylguanine-DNA methyltransferase (MGMT) gene promoter methylation. Since its approval by the US Food and Drug Administration for the treatment of patients with recurrent GBM in 2009, the efficacy of the anti-vascular endothelial growth factor (VEGF)-A humanized monoclonal antibody bevacizumab in combination with SRS has been evaluated in several studies [ 38 , 50 , 52 ].…”
Section: Survival Outcomes and Toxicitymentioning
confidence: 99%
“…With respect to the retrospective nature and small numbers of patients, available data suggest increased survival rates with SRS and systemic therapies compared to SRS alone [ 38 , 44 , 46 , 48 , 51 ]. The reported overall survival time after concurrent SRS and temozolomide is around 9–15 months; some [ 44 , 46 , 48 , 51 ], but not all [ 36 , 47 ], studies showed significant survival benefit following chemoradiation over SRS alone, especially in patients with O 6 -methylguanine-DNA methyltransferase (MGMT) gene promoter methylation. Since its approval by the US Food and Drug Administration for the treatment of patients with recurrent GBM in 2009, the efficacy of the anti-vascular endothelial growth factor (VEGF)-A humanized monoclonal antibody bevacizumab in combination with SRS has been evaluated in several studies [ 38 , 50 , 52 ].…”
Section: Survival Outcomes and Toxicitymentioning
confidence: 99%
“…Kong et al reported a RN rate of 24% and Imber et al of 16% after EBRT with 60 Gy in 2 Gy fractions and a single fraction re-irradiation with 16 Gy. This is equal to a summed EQD2 of 120 Gy and a BED of 200 Gy 3 for late reacting tissue [ 22 , 23 ]. Based on historical data, radiogenic complications after SBT alone occurred in 9% for tumors with a diameter < 4 cm and higher complication rates (up to 25%) were reported for tumors harboring larger diameters (≥ 4 cm) [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, this trial was discussed, because SRS was conducted before external radiation, and carmustine was not used as a routine treatment in GBM patients. Some subsequent retrospective studies on SRS revealed that SRS can be used as a safe and effective treatment for HGG patients with small recurrent tumors (44)(45)(46). Morris et al (47) reported that 45 patients with recurrent GBM were treated with SRS and bevacizumab.…”
Section: Srsmentioning
confidence: 99%